Exploring Habitus and Writer Identities: An ethnographic study of writer identity construction in the FET Phase at two schools in the Western Cape - Van Heerden, Michelle (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
Globalisation processes have resulted in increasingly pluralistic societies, a phenomenon with ripple effects in contexts such as universities, which now provide access to heterogeneous student populations with diverse rituals, beliefs, cultures and languages. For this reason, deficit discourses that frame students as underprepared for the demands of tertiary studies are a global phenomenon (Boughey, 2003; Lillis, 2003; Lea & Street, 1998). Furthermore, the different identities, histories and dispositions (Bourdieu, 1990) of students result in hybrid linguistic repertoires, with some repertoires being more powerful than others (Blommaert, 2001; Blommaert, Collins &Slembrouck, 2005; Rampton, 2003). Therefore, having access to the preferred linguistic repertoire - in most cases standard English - is an asset, because this repertoire is more closely aligned than others to tertiary education practices and discourses.